PROBLEMS IN EARLY MARRIAGE AND FAMILY RELATIONSHIP SYSTEM DURING ADOLESCENCE (International journal of artificial intelligence, 2024)
This article analyzes the impact of family formation, early marriages on the fate of young people and its social, psychological and economic aspects. Also, the problems in our society regarding family and marriage and issues of managing this process are described.